USING SHORT VIDEOS TO IMPROVE 7TH GRADE STUDENTS' VOCABULARY MASTERY - Azis, Astuti; Setianto, Daud (International Journal of English Language and Pedagogy, 2023)
This research focuses on how to improve students’ English vocabulary mastery using short videos. The subject of the research was Class VII-A SMP Pangudi Luhur Santo Yusup Semarang with a total of 24 students. The research was conducted in semester 2 of the 2022/2023 academic year in two cycles. Data was collected using observation techniques and qualitative and quantitative data collection. In pre-cycle activities, less than 50% of students get satisfactory formative test results, and students tend to be passive during the learning process. In cycle 1, there was a change in student scores, more than 60% of students got satisfactory results, and student-teacher engagement also increased. During cycle 2, 80% of students got satisfactory learning outcomes through changes in formative test scores. It can be concluded that the use of video is beneficial to improve students’ mastery of English vocabulary